Examining the consumers' preference towards adopting the mobile payment system. (5th December 2019) - Kumar, A. Senthil; Palanisamy, Y. Arun
The research examines the drivers and shared preferences of consumers towards adopting the mobile payment systems in the Indian context. A survey was conducted with 152 respondents in the Coimbatore City, State of Tamil Nadu, India. A structured questionnaire was developed using the technology acceptance model (TAM) framework constructs. The multivariate tools like factor analysis and cluster analysis were used for data analysis. The results reveal that perceived usefulness and ease of using mobile payments primarily drive the preferences of consumers. The common preferences among users and non-users of mobile payment services were classified and analysed. The insights from the classification have managerial implications, and the paper discusses them in detail.